USING ARTIFICIAL INTELLIGENCE IN HUMAN RESOURCE MANAGEMENT PROCESSES - A. V. Blinnikova; D. K. Ying (Вестник университета)
During the digital transformation, artificial intelligence technologies are actively developed and implemented in the organization’s management processes. This trend also applies to human resource management. The purpose of this article is to substantiate the benefits of using artificial intelligence tools in human resource management for organizations. Current state of human resource management has been analysed in the article, its main problems have been defined. The opportunities offered by artificial intelligence technologies offer in the field of human resources as well as the problems companies face in their implementation have been considered. Practical examples of the use of artificial intelligence tools such as chatbots, mood analysis technologies, voice assistants, facial recognition system in the field of human resource management have been given.